PEMANFAATAN REGRESI LINIER SEDERHANA DALAM PENELITIAN PENDIDIKAN DASAR: KAJIAN LITERATUR SISTEMATIS - Khoirul Bariah Rambe; Nahdah Faizah Harahap; Almira Amir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to review the utilization of simple linear regression in primary education research through a systematic literature review. The methodology involves searching and selecting scholarly articles from reputable academic databases, based on specific inclusion and exclusion criteria, followed by content analysis to identify applications of simple linear regression in primary education studies. The findings indicate that simple linear regression is highly effective for analyzing relationships between variables, such as the impact of environmental factors on students’ academic performance. Additionally, the review highlights various applications, including program evaluation and the analysis of success determinants in learning. The results suggest that simple linear regression is a relevant and accessible statistical tool for primary education research. This review is expected to serve as a valuable reference for researchers and educators in selecting appropriate statistical methods for their studies.